Epidemiology and Pathophysiology of Restless Legs Syndrome - Kim, Tae-Joon; Kim, Min Hye (Journal of sleep medicine, 2025)
Restless legs syndrome (RLS) is a chronic neurological disorder characterized by an overwhelming urge to move the legs, typically accompanied by unpleasant sensations that worsen at rest, particularly in the evening and night. The diagnosis of RLS is primarily symptom-based, with a recent revision of the diagnostic criteria in 2012 emphasizing the distinction between true RLS and conditions that mimic it, such as leg cramps or arthritis. This has led to variations in the prevalence of RLS, particularly in different diagnostic criteria and methodologies, with higher rates observed in simple questionnaires and lower rates in differential diagnoses and detailed interviews. The pathophysiology of RLS is complex and involves dopaminergic dysfunction and brain-specific iron deficiency. Dopamine dysregulation contributes significantly to this disorder, as evidenced by the efficacy of dopaminergic treatment. Additionally, iron deficiency in the brain, especially in areas such as the striatum and substantia nigra, plays a critical role in RLS, with studies indicating reduced iron levels in affected individuals and improvement in symptoms following iron supplementation. This article provides an in-depth review of the epidemiology and pathophysiology of RLS, particularly in Asia, focusing on the importance of accurate diagnostic criteria and the roles of dopamine and iron in the development of this disorder.